Impacts of a national lockdown on smallholder farmers’ income and food security: Empirical evidence from two states in India - Ceballos, Francisco; Kannan, Samyuktha; Kramer, Berber (Elsevier, 2020)
In early 2020, the unprecedented nature of COVID-19 prompted India, among many other countries, to put in place stark measures to stem the virus’ spread and the cost of human lives. We analyze data from phone-based surveys on disruptions to agricultural production and food security, administered with 1515 smallholder producers in the states of Haryana and Odisha. We find substantial heterogeneity in how the lockdown affected farmers in these two states, which is likely related to existing structural differences in market infrastructure and to differences in state-specific COVID-related policies. In Odisha, where mechanization is limited, farmers spent more on labor to harvest their crops, and distress selling was more prevalent due to the absence of a well-functioning procurement system for their crops. In Haryana, preexisting market infrastructure allowed the state to sustain procurement at stable prices, limiting impacts on smallholder production. As consumers, farmers in Haryana faced more disruptions than those in Odisha, due to reduced availability of foods in the markets, whereas farmers in Odisha benefited from more diverse cropping patterns and increased local supply of foods following transport restrictions.